Examining the Mediating Role of Work Motivation in the Relationship between Principals’ Leadership, Work Climate, and Kindergarten Teachers’ Performance - Oxtavia, Lailil; Karwanto, Karwanto; Haq, Mohammad Syahidul (Journal of English Language and Education, 2025)
This study investigates the influence of principals’ leadership and the work climate on teachers’ performance, with work motivation positioned as a mediating factor. A quantitative research design was applied through a survey approach. The study involved kindergarten teachers in the North Bekasi District, with 77 respondents selected using purposive sampling. Data collection was carried out using a Likert-scale questionnaire, and the data were analyzed through Partial Least Square–Structural Equation Modeling (PLS-SEM). The findings reveal that the work climate has a positive and significant impact on teachers’ performance, whereas principals’ leadership does not show a significant effect on teachers’ performance or work motivation. In addition, the work climate does not significantly affect work motivation. Work motivation, however, has a positive and significant influence on teachers’ performance, although it does not function as a mediator in the relationship between principals’ leadership and teachers’ performance, nor between the work climate and teachers’ performance. Overall, the results indicate that teachers’ performance is more strongly shaped by a supportive work environment and the level of teachers’ motivation. Consequently, efforts to improve teachers’ performance and enhance educational quality should prioritize the creation of a positive work climate and the strengthening of teachers’ work motivation.